Automated maxillofacial reconstruction software: development and evaluation. Issue 2 (3rd March 2020) - Kim, Hannah; Son, Tae-Geun; Cho, Hyunchul; Shim, Eungjune; Hwang, Bo-Yeon; Lee, Jung-Woo; Kim, Youngjun
ABSTRACT: In this paper, we propose a surgical planning system to automate the preoperative planning for mandibular reconstruction with a fibula free flap. We designed surgical guides with user-friendly interfaces based on the surgical plans. In this system, the osteotomy planes of the fibula and the position of each fibular segment are calculated automatically by adopting the mandibular geometry to restore the original mandibular shape. From the formulated plan, patient-specific resection guides can be easily designed. In retrospectively conducted evaluations with nine patients' data, the average reconstruction error between the reference plans of experts and the reproduced plans of the proposed automatic methods was 0.23 ± 0.27 mm, and the automatic planning time was 4 min and 25 s on average. We expect that the proposed system will simplify surgical planning, increase the surgical accuracy, and improve patient safety.